Screening of antimicrobials, fragrances, UV stabilizers, plasticizers and preservatives in sewage treatment plants (STPs) and their risk assessment in India. (December 2022) - Vimalkumar, Krishnamoorthi; Mayilsamy, Murugasamy; Arun, Elayaraja; Gobinath, Balasubramanian; Prasanth, Saravanan; Nikhil, Patil Nishikant; Krishna-Kumar, Selvaraj; Srimurali, Sampath; Mkandawire, Martin; Babu-Rajendran, Ramaswamy
Abstract: Community/industrial wastewater is the prime source of anthropogenic chemicals, its treatment is often a daunting task and unaffordable for many countries. Emerging Contaminants (ECs) have been drained into wastewater after continuous use/misuse and Conventional treatments in STPs do not remove them completely. ECs including antimicrobial agents, synthetic musks, Benzotriazole UV stabilizers (BUVSs), plasticizers, and preservatives are frequently reported in environment, and cause health effects to non-target organisms. Monitoring of ECs is important to understand their status in aquatic environment. Hence, it was aimed to monitor ECs (n = 21) from 11 STPs in Tamil Nadu, India. The detection frequency of most of these analytes was >90%. Antimicrobials ranged from 247 to 22, 714 ng/L and 11–14, 369 ng/L in influents and effluents, respectively. The synthetic musks were in the order of Tonalide > Galaxolide > Musk Ketone. BUVSs ranged from 4 to 1632 ng/L (influents) and < LOD to 29, 853 ng/L (effluents). Concentration of phthalates in influents and effluents were < LOD - 11, 311 ng/L and < LOD - 17, 618 ng/L, respectively. Parabens were found in the order of Prophyl > Methyl > Ethyl > Butyl in influents and Methyl > Prophyl > Butyl > Ethyl in effluents. Mass loads of ECs through STPs were found as antimicrobials > plasticizers > fragrances > BUVSs > Preservatives. This study reveals increasing usage of ECs and inadequate treatment processes at STPs in India. Also helps to adopt suitable treatment processes to remove ECs from wastewater and to reuse the wastewater. Graphical abstract: Image 1 Highlights: 11 STPs were screened for ECs from major cities in Tamil Nadu, southern India. Elevated levels of phthalates and antimicrobial agents in both influents and effluents were observed. A strong positive correlation found between the groups of antimicrobial agents and UV stabilizers in effluent. Hazard Quotient >1 for ECs (DEHP, UV328 and TCC) were obtained in effluents of Indian STPs. First report on the fate of Synthetic musks and BUVSs, and mass load of ECs in Indian STPs.